1988
DOI: 10.1161/01.hyp.11.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary receptor modulation of plasma renin activity in normotensive and hypertensive subjects.

Abstract: SUMMARY Cardiopulmonary receptors modulate renin release in several animal species. However, their involvement in reflex control of this humoral substance in humans is controversial. Furthermore, no information is available on the alteration of this control in hypertension. We studied the modulation of plasma renin activity (radioimmunoassay) in 12 normotensive subjects and in 12 age-matched subjects with untreated hypertension of mild or moderate degree. Cardiopulmonary receptors were stimulated by increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…[15][16][17] Because cardiopulmonary receptors are sensitive to changes in central blood volume during both leg raising and lower body negative pressure, the alterations in cardiopulmonary receptor stimuli were assessed from the changes in left ventricular enddiastolic diameter. 18 The reflex responses were assessed from the changes in forearm circulation and plasma norepinephrine because of the major impact of cardiopulmonary receptor activity on both these variables. '5,1619 1224 Circulation Vol 82, No 4, October 1990 responsiveness to a neurogenic stimulus unrelated to that originating from cardiopulmonary receptors.20…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17] Because cardiopulmonary receptors are sensitive to changes in central blood volume during both leg raising and lower body negative pressure, the alterations in cardiopulmonary receptor stimuli were assessed from the changes in left ventricular enddiastolic diameter. 18 The reflex responses were assessed from the changes in forearm circulation and plasma norepinephrine because of the major impact of cardiopulmonary receptor activity on both these variables. '5,1619 1224 Circulation Vol 82, No 4, October 1990 responsiveness to a neurogenic stimulus unrelated to that originating from cardiopulmonary receptors.20…”
Section: Methodsmentioning
confidence: 99%
“…22,23 When involvement of arterial baroreceptors is avoided, stimulation of cardiopulmonary receptors causes a general withdrawal of the sympathetic outflow, but the effect on renal sympathetic tone is most pronounced. Furthermore, it has been shown that cardiopulmonary receptors mediate systemic renin release through …”
Section: Sodium Sbp and Effective Total Vascular Compliancementioning
confidence: 99%
“…In subjects with mild-to-moderate essential hypertension, this reninreflex modulation remains operative but exerts reduced effectiveness compared with normal subjects. 22 Finally, in hypertensive subjects, total blood volume and effective compliance of the vascular bed are significantly reduced. In the presence of preserved cardiac performance, central venous pressure is increased slightly but significantly.…”
Section: Safar Et Al Sodium and Vascular Stiffness 205mentioning
confidence: 99%
See 1 more Smart Citation
“…TM In addition to modulating the neural response to orthostatic stress, it has also been demonstrated that in healthy man cardiopulmonary baroreceptors modulate renin release. 19 There are other receptors located within the ventricle; these stretch receptors have recently been shown to be important in modulating changes in forearm vascular resistance in response to changes in pressure. 2~ High pressure mechanoreceptors are situated in the walls of the aortic arch and in the carotid sinus; these stretch receptors have nerve endings embedded in the adventitial layer of the arterial wall.…”
Section: Discussionmentioning
confidence: 99%